2018
DOI: 10.1039/c7fo01802a
|View full text |Cite
|
Sign up to set email alerts
|

Ambient storage of microencapsulated Lactobacillus plantarum ST-III by complex coacervation of type-A gelatin and gum arabic

Abstract: Ambient storage of dry powdered probiotics is necessary for manufacturer's cost reduction and customer's convenience. Complex coacervation is a promising microencapsulation technique. In this work, a probiotic matrix of type-A gelatin/gum arabic/sucrose (GE/GA/S) with high coacervation pH was designed, based on the alkaline isoelectric point of type-A gelatin. Bacterial survival during ambient storage at room temperature and certain relative humidity were detected. To clarify the protection factors of the coac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 28 publications
0
30
1
Order By: Relevance
“…Microgels can be fabricated from a combination of biopolymers using complex coacervation, which involves mixing a negatively charged biopolymer with a positively charged one (Saravanan, and Panduranga, ). Complex coacervation has been reported to be advantageous in terms of high cell‐entrapment efficiency, enhanced functional performance, and good suitability for scaling up (De Prisco & Mauriello, ; Zhao et al., ). Moreover, complex coacervates can be designed to promote the complete release of encapsulated probiotics from biopolymer microgels (Bosnea et al., ).…”
Section: Microencapsulation Of Probioticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microgels can be fabricated from a combination of biopolymers using complex coacervation, which involves mixing a negatively charged biopolymer with a positively charged one (Saravanan, and Panduranga, ). Complex coacervation has been reported to be advantageous in terms of high cell‐entrapment efficiency, enhanced functional performance, and good suitability for scaling up (De Prisco & Mauriello, ; Zhao et al., ). Moreover, complex coacervates can be designed to promote the complete release of encapsulated probiotics from biopolymer microgels (Bosnea et al., ).…”
Section: Microencapsulation Of Probioticsmentioning
confidence: 99%
“…Moreover, complex coacervates can be designed to promote the complete release of encapsulated probiotics from biopolymer microgels (Bosnea et al., ). Recent studies have reported that different biopolymer combinations can be used to successfully assemble complex coacervates suitable for probiotic delivery: whey protein isolate/gum arabic (WPI/GA) (Eratte et al., ), WPI/κ‐carrageenan (Hernandez‐Rodriguez, Lobato‐Calleros, Pimentel‐Gonzalez, & Vernon‐Carter, ), WPI/GA/alginate (Bosnea, Moschakis, Nigam, & Biliaderis, ), gelatin/GA (da Silva et al., ; Zhao et al., ), gelatin/alginate (Yao et al., ), and starch/alginate (Pankasemsuk et al., ). For instance, encapsulation of probiotics in alginate‐gelatin microgels formed through electrostatic complexation has been shown to improve the viability of L. salivarus Li01 after high temperature treatments, long‐term storage, and gastrointestinal passage (Yao et al., ).…”
Section: Microencapsulation Of Probioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Second, ambient storage of probiotics becomes more and more important due to the consumer needs for ambient probiotic foods, but the probiotic survival during ambient storage is poor. 7,8 One of the challenges of dry probiotic preparations is the moisture sorption during ambient storage, which decreases the glass transition temperature and leads to a significant acceleration of the inactivation of probiotic bacteria. [9][10][11] Therefore, in order to solve the above two challenges of the dry probiotic cells, it is necessary to design probiotic microcapsules to simultaneously improve probiotic survivals in simulated digestive juices and during ambient storage.…”
Section: Introductionmentioning
confidence: 99%
“…WPI and sucrose could provide good probiotic protection during drying and ambient storage. 7,[23][24][25] Alginate was the main gelling matrix with calcium ion during microcapsule preparation. The method of external emulsification was employed to prepare microcapsules, which is beneficial to obtain small microcapsules.…”
Section: Introductionmentioning
confidence: 99%